Links across disabilities: unveiling associations between functional domains - J. Dalal; S. Mitra; A. James; M. Rivas Velarde (BMC, 2024)
Abstract Background Persons with disabilities experience higher risks of mortality as well as poorer health as compared to the general population. The aim of this study is to estimate the correlations between functional difficulties across several domains in six countries. Methods National census data with questions on disability from six countries (Mauritius, Morocco, Senegal, Myanmar, Vietnam, and Uruguay) was used in this study. We performed logistic regressions to assess the extent to which having a functional difficulty in one domain is correlated with having a functional difficulty in each of the other domains and report weighted odds ratios (ORs) overall and within age-groups ('18-44' years and '45+' years). Models adjust for age, sex, and location (rural or urban). Sensitivity analyses around different choices of predictors and response variables were conducted. Findings For all countries, reporting a functional difficulty in one domain was consistently and significantly positively correlated with reporting a functional difficulty in other domains (overall) and for each of the two age-groups considered - '18-44' years and '45+' years. All ORs were greater than one. Cognition, mobility, and hearing were the domains that were the most correlated ones with other domains. The highest pairwise correlations were for i/ hearing and cognition; ii/ mobility and cognition. Results were robust to changing the severity thresholds for functional difficulties. Across countries, Uruguay, the only high-income country among the six countries under study, had the lowest correlations between functional domains. Conclusions There are consistent positive associations in the experience of functional difficulties in various domains in the six countries under study. Such correlations may reflect barriers to social services including healthcare services and resources (e.g. assistive devices) that may lead to an avoidable deterioration of functioning across domains. Further research is needed on the trajectories of functional difficulties and on structural barriers that people with functional difficulties may experience in their communities and in healthcare settings in particular. This is important as some functional difficulties may be preventable.